2021
DOI: 10.1021/acs.est.1c00616
|View full text |Cite
|
Sign up to set email alerts
|

Significant Reductive Transformation of 6:2 Chlorinated Polyfluorooctane Ether Sulfonate to Form Hydrogen-Substituted Polyfluorooctane Ether Sulfonate and Their Toxicokinetics in Male Sprague–Dawley Rats

Abstract: 6:2 chlorinated polyfluorooctane ether sulfonate (6:2 Cl-PFESA) was previously shown to undergo limited dechlorination in rainbow trout to yield 6:2 hydrogen-substituted polyfluorooctane ether sulfonate (6:2 H-PFESA) as the sole metabolite. However, the biotransformation susceptibility of 6:2 Cl-PFESA has not been investigated in mammals and the biological behavior of 6:2 H-PFESA has not been defined in any species. We investigated the respective transformation products of 6:2 Cl-PFESA and 6:2 H-PFESA and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 69 publications
3
32
0
Order By: Relevance
“…6:2 H-PFESA was the sole biotransformation product identified in all the active treatments (Figure S1) but was absent from all the control groups. This finding was in agreement with previous investigations that reported that 6:2 H-PFESA was the sole biotransformation product of 6:2 Cl-PFESA in fish and rats . Furthermore, the molar mass balance in experimental bottles was calculated during single dose and re-dose cycles by comparing the final summed masses of 6:2 Cl-PFESA and 6:2 H-PFESA with the initial dose of 6:2 Cl-PFESA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6:2 H-PFESA was the sole biotransformation product identified in all the active treatments (Figure S1) but was absent from all the control groups. This finding was in agreement with previous investigations that reported that 6:2 H-PFESA was the sole biotransformation product of 6:2 Cl-PFESA in fish and rats . Furthermore, the molar mass balance in experimental bottles was calculated during single dose and re-dose cycles by comparing the final summed masses of 6:2 Cl-PFESA and 6:2 H-PFESA with the initial dose of 6:2 Cl-PFESA.…”
Section: Resultsmentioning
confidence: 99%
“…Screening of unknown metabolites of 6:2 Cl-FPESA was performed with high-performance liquid chromatography (HPLC) coupled to a high-resolution quadrupole orbitrap mass spectrometer (Q Exactive, Thermo Fisher Scientific). The in-source fragmentation scanning strategy was used to flag PFASs as introduced by Liu et al The instrumental operation conditions are provided in our previous work …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reductive dechlorination was also reported as the major biotransformation pathway for other Cl-terminal PFAS structures, such as 6:2 Cl-PFESA and F-53B, but no defluorination was observed for those compounds. [21][22][23] Here, we also observed a defluorinating pathway of Cl-C5a, forming TP238_Cl-C5a (perfluoropentanedioic acid, PFPediA) (Figure S13B). We inferred that Cl-C5a first underwent hydrolytic dechlorination at the terminal Clsubstitution forming an unstable fluoroalcohol moiety, which was subject to spontaneous eliminative and hydrolytic defluorination forming PFPediA (Figure 5B).…”
Section: Enhanced Anaerobic Microbial Defluorination Of Cl-terminal P...mentioning
confidence: 66%
“…There are only a few studies on the biotransformation of specific Cl-PFAS by microbes, fish, and rats, where only biodechlorination was reported. [21][22][23] Whether and how environmental microbes can transform and defluorinate various Cl-PFAS structures is yet unknown. So far, microbial defluorination of organofluorines with transformation pathways or mechanisms demonstrated was only limited to the hydrolytic defluorination of monofluoroacetate (MFA), 24 the aerobic defluorination of fluorinated aromatics and sulfonates, [25][26][27][28] the aerobic and anaerobic defluorination of fluorotelomers mainly via /βoxidation-like pathways, [29][30][31][32][33][34][35][36] as well as the anaerobic defluorination of unsaturated perfluorinated compounds.…”
Section: Introductionmentioning
confidence: 99%